Students' Morals Toward Educators Syeikh Abdurrauf As-Singkily's Perspective in The Book Turjuman Al-Mustafid - Maha, M Fatahurahman; OK, Azizah Hanum; Harahap, Muhammad Riduan (AJIS: Academic Journal of Islamic Studies, 2024)
Â This research aims to analyse 1). Biography of Syeikh Abdurrauf As-Singkily, 2). The values of students' moral education towards educators from the perspective of Syeikh Abdurrauf As-Singkily, 3). The relevance of students' morals towards educators from the perspective of Syeikh Abdurrauf As-Singkily with the goals of national education. This type of research is a qualitative approach to character studies with data analysis techniques using content analysis. The results of this research are: 1). Syeikh Abdurrauf was born in 1024 H/ 1615 M, his parents were Syeikh Ali Fansuri and Aminah, he grew up in the village of Ukhuk Datar Suro, as a teenager Syeikh Abdurrauf As-Singkily studied in the land of Fansur (Barus) then continued his education in Aceh studying with Syeikh Syamsudin Sumatrani and then left for Arabia in 1642 AD, after the death of Syeikh Ahmad Qusya His teacher in Arabia, Syeikh Abdurrauf returned to Aceh during the sultanate of Tuan Iskandar Muda and became the Mufti of the Aceh kingdom at that time. Then Syeikh Abdurrauf became the pioneer of the Syattariyah order and had several of them, including Burhanuddin Ulakan, Muhyi Pamijahan, and Baba Daud Al-Jawi. Some of his relics are in the form of a stick, a handwritten Al-Qur'an and books, one of which is the book Turjuman Al-Mustafid. 2). The moral values of students towards educators are, patience, obedience, do not ask something that has not been taught, pay attention and listen carefully, do not whisper, do not disturb the teacher's break time, be polite in speaking, ask nicely, do not deny the teacher, do not raise your voice. 3). This research is relevant to the National Goals in shaping the character, morals, and ethics of students and the integration of knowledge, but is less relevant in the development of today's era and technology.